Circulação da instrução programada no Brasil (1960-1980) - Eustaquio Jose de Souza Junior (2015)
The paper presented here is intended to characterize the processes of reception and circulation of the programmed instruction (PI) in Brazil. This thesis defends that the IP consisted of technology that contributed to the consolidation of the technological discourse in national academic circles and by doing that it acted as a vehicle of communication for the learning theory in the Brazilian context. To prove that, three independent studies were conducted, and although correlated, which one of them had their individual objectives: 1) the characterization of programmed instruction through its production of teaching devices called "teaching machines" and textbooks aligned to its principles from the 1920s in the US; 2) the description and analysis of the reception and circulation of programmed instruction in Brazil, through quantitative and qualitative studies of documentary corpus of articles, abstracts and reviews published in national journals in the areas of education and psychology between the 1960s and 1970s and; 3) understanding of PI local reception from the analysis of oral sources, working in PI at UFMG in the 1960s and 1970. The findings indicated that the PI technology that was to answer the principles of systematization of teaching/learning, recommending the following aspects: a) there should be setting behavior / performance objectives as the pedagogical process; b) the program must provide the presentation of the content to be worked in stages; c) the learner's own pace should be respected, and d) necessarily be immediate and contingent feedback upon the student response. It was published a series of studies and technical applications in the US and Europe mostly between the 1950s and 1970s. In Brazil, a record of academic introduction was obtained from the 1960s, followed by the publication of several local manual and translation on the subject, as well as its adoption as a teaching resource in some educational settings. The conclusions of integrated studies indicated that IP was a technological product designed from different theoretical/methodological biases that it appropriated, sometimes as derivation of operant learning theory, or as the operation of a teaching technique. It was also found that the PI reception in Brazil was affected by the action group committed to psychological theory of learning linked to the notion of operant behavior. The PI connection with experimental studies on animals along with the working theory of US origin, were guidelines used to support the technique of this movement in Brazil. These characteristics seem to have competed for the decrease in circulation in Brazil, while, emerged other didactic propositions supported by the operant theory.